(untitled) (NPRC Journal of Multidisciplinary Research, 2024)
Adversarial Machine Learning (AML) has emerged as both a challenge and an opportunity in the realm of cybersecurity. As malicious actors leverage advanced techniques to deceive machine learning models, the need for robust AI-driven defenses becomes paramount. This paper explores the intersection of AML and cybersecurity, focusing on innovative threat detection and mitigation strategies. We delve into the mechanisms of adversarial attacks, including evasion, poisoning, and model inversion, and examine their impact on critical security systems. Furthermore, we present cutting-edge approaches for enhancing the resilience of machine learning models, such as adversarial training, robust optimization, and ensemble methods. Through practical case studies and simulations, we demonstrate how AML techniques can detect and neutralize cyber threats in real-time, providing a proactive framework for securing networks, data, and applications. This work underscores the importance of integrating AML strategies into cybersecurity protocols, paving the way for more adaptive and intelligent defense mechanisms in the face of evolving threats.